25 Atrial remodelling in patients affected by chronic heart failure in therapy with sacubitril/valsartan. (8th December 2021) - Magnesa, Michele; Mazzeo, Pietro; Fortunato, Martino; Mennella, Raffaele; Tricarico, Lucia; Correale, Michele; Croella, Francesca; Mallardi, Adriana; Leopizzi, Alessandra; Ceci, Vincenzo; Alfieri, Simona; Iacoviello, Massimo; et al.
Abstract: Aims: Left atrial (LA) enlargement has been demonstrated to be a predictor of adverse cardiovascular outcomes, such as atrial fibrillation (AF), heart failure (HF), and cardiovascular death. Previous studies showed left ventricle ejection fraction (LVEF) improvement and reverse remodelling can be achieved after therapy with sacubitril/valsartan in real-world settings. We sought to investigate the association between left atrial (LA) structural and functional remodelling in patients with chronic HF after therapy with sacubitril/valsartan. Methods and results: Patients affected by chronic HF with LV dysfunction (LVEF < 35%), NYHA functional class II–III were followed up between September 2019 and March 2020. All patients underwent clinical and echocardiography Follow-up at baseline and after 6 months of therapy with sacubitril/valsartan. Measures of LA structure [LA end-systolic volume (LAESV)] and function [ left atrial emptying fraction (LAEF), peak atrial longitudinal strain (PALS), LA conduit strain and peak atrial contraction strain (PACS)] were calculated. A total of 47 patients (median age 66 ± 7.97, male gender 85%, mean LVEF 28.33 ± 5.61%) were enrolled. The left atrial strain parameters (PALS and LA conduit) resulted higher at 6 months follow-up respect to baseline values, (14.68 ± 7.16 vs. 18.67 ± 8.03, P  < 0.001, and −7.61 ± 4.07 vs. −9.71 ± 5.23, P  = 0.007, respectively). Conclusions: Treatment with sacubitril/valsartan in patients with HFrEF is associated with an improvement in LA functional remodelling in a real-world scenario.